1977
DOI: 10.1111/j.1476-5381.1977.tb07487.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF INDOMETHACIN AND RELATED DRUGS ON THE CALCIUM ION‐DEPENDENT SECRETION OF LYSOSOMAL AND OTHER ENZYMES BY NEUTROPHIL POLYMORPHONUCLEAR LEUCOCYTES In vitro

Abstract: 1Rabbit isolated peritoneal neutrophil polymorphonuclear leucocytes were depleted of calcium by exposure for 1 h to calcium‐free bathing fluid at 4°C. 2Addition of calcium ions to the previously calcium‐depleted cells during incubation at 37°C stimulated the release of β‐glucuronidase and of lysozyme but not of lactate dehydrogenase. 3Low concentrations of indomethacin, flufenamate or salicylate, such as those which occur in the blood plasma after therapeutic doses of these drugs, selectively inhibited the cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…macrophages and PMNs) that mediate inflammatory reactions (Lowe and Turner 1973;Northover 1977;Smith 1977;Riches et al 1981;Riches and Stanworth 1982;Wildfeuer 1983;Glaumann et al 1985;. While CQ did not appear to affect release of enzymes from nonphagocytozing cells (Northover 1977), the stimulation of phagocytosis by serum treated zymosan was found to be inhibited by CQ (Smith 1977;Wildfeuer 1983).…”
Section: Lysosomotropic Activitymentioning
confidence: 94%
See 1 more Smart Citation
“…macrophages and PMNs) that mediate inflammatory reactions (Lowe and Turner 1973;Northover 1977;Smith 1977;Riches et al 1981;Riches and Stanworth 1982;Wildfeuer 1983;Glaumann et al 1985;. While CQ did not appear to affect release of enzymes from nonphagocytozing cells (Northover 1977), the stimulation of phagocytosis by serum treated zymosan was found to be inhibited by CQ (Smith 1977;Wildfeuer 1983).…”
Section: Lysosomotropic Activitymentioning
confidence: 94%
“…macrophages and PMNs) that mediate inflammatory reactions (Lowe and Turner 1973;Northover 1977;Smith 1977;Riches et al 1981;Riches and Stanworth 1982;Wildfeuer 1983;Glaumann et al 1985;. While CQ did not appear to affect release of enzymes from nonphagocytozing cells (Northover 1977), the stimulation of phagocytosis by serum treated zymosan was found to be inhibited by CQ (Smith 1977;Wildfeuer 1983). Riches et al (1981) and Riches and Stanworth (1982) observed that mouse peritoneal macrophages incubated with CQ and quinine showed time-dependent and concentration-dependent inhibition of the release from lysosomes of N-acetyl-b-D-glucosaminidase and b-galactosidase from macrophages; the effective concentration range being 50-300 lM for CQ.…”
Section: Lysosomotropic Activitymentioning
confidence: 94%
“…Instead, inhibition of both cortical prostanoids synthase and prostacyclin receptor activation may be needed to blunt the cerebrovascular CO 2 reactivity. Alternatively, it is possible that INDO may alter cerebrovascular function via non-prostaglandin pathways, such as inhibition of histamine release (Konig et al 1987), calcium channel blockade (Northover 1977), potentiation of lipoxygenase pathway (Docherty and Wilson 1987), modification of extracellular pH (Wang et al 1993), INDO's scavenging effect on inhibition of superoxide generation (Pourcyrous et al 1993), or via increases in endothelin-1 (Therkelsen et al 1994). Most noteworthy is the finding by Wang et al (1993), which showed that INDO abolished the acetazolamide-induced increase in CBF.…”
Section: Indomethacinmentioning
confidence: 98%
“…If the action of ibuprofen, indomethacin and meclofenamate in stimulating glycogenolysis is independent of cyclo-oxygenase inhibition, their action might be through alterations in either cyclic AMP generation or (Exton, 1982). Recent reports from other laboratories provide evidence that drugs such as ibuprofen can interfere with intracellular calcium handling at the concentrations reported here to increase glycogenolysis (Northover, 1973;Northover, 1977;Burch et al, 1983). To determine whether ibuprofen could directly affect cyclic AMP production, the effect ofthe drug on adenylate cyclase activity was studied on isolated hepatocyte membranes.…”
Section: Discussionmentioning
confidence: 93%